Motor imagery in spinal cord injury patients: Moving makes the difference. Issue 2 (15th May 2013) - Fiori, Federico; Sedda, Anna; Ferrè, Elisa Raffaella; Toraldo, Alessio; Querzola, Matteo; Pasotti, Fabrizio; Ovadia, Daniela; Piroddi, Chiara; Dell'Aquila, Roberta; Redaelli, Tiziana; Bottini, Gabriella
<x xml:space="preserve">Abstract</x> Both real action control and execution and motor imagery abilities require knowledge of the spatial location of body parts, in other words efference copy information and feedbacks from the sensory system (Frith et al., 2000, Philos. Trans. R. Soc. Lond. B. Biol. Sci., 355, 1771). Spinal cord injuries induce severe motor disability, due to a damage of the descending motor pathways (Cramer et al., 2007, Exp. Brain. Res., 177, 233). Patients' motor imagery competences are variably reported as either normal or defective (Decety & Boisson, 1990, Eur. Arch. Psychiatry Clin. Neurosci., 240, 39; Lacourse et al., 1999, Behav. Brain Sci., 104, 73). We explored biomechanical constraint effects in Spinal Cord Injury (SCI) patients, as they are considered the most reliable indexes of motor imagery abilities (Parsons, 1987b, Cogn. Psychol., 19, 178). Sixteen spinal cord injuries patients and 16 neurologically unimpaired subjects have been administered with (1) the Hand Laterality Task (HLT), in which subjects were asked to judge the laterality of a rotated hand; and (2) the Mirror Letter Discrimination Task (MLD), in which subjects were asked to judge if a rotated character was in its correct upright position or mirror‐reversed form. Our patients did not present the effect of stimulus orientation, neither did they show any effect related to biomechanical constraints. Based on these data, the hypothesis is that SCI patients' performance may be ascribed to the use of a different strategy to solve the tasks, based on memory rather than on mental rotation.